INFLECTION IN TOPOSA, A VSO LANGUAGE IN MORPHO-SYNTACTIC THEORY (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper presents a morpho-syntactic approach to inflection as suggestedunder the new Minimalist Program (Chomsky 1993/1995). The languageunder consideration is Toposa, an Eastern Nilotic language which is highlyinflectional and derivational. It belongs to the Teso-Turkana subgroup ofEastern Nilotic and is spoken in the south-eastern corner of Southern Sudan.Firstly, the paper deals with inflection in a VSO language and suggests thatthe order of the tense and agreement heads is alternated. The change in theorder of heads is morphologically motivated by the tense tonal features ofthe language. Secondly, it makes a choice between the agreement analysisand the subject incorporation theory, showing that the latter theory reflectsmore accurately the reality of Toposa data. Thirdly, it considers the role ofthe overt NP in the subject incorporation theory. It concludes with the claimthat the occurrence of personal pronouns carries a [+focus] feature.